The First Emperor : Caesar Augustus and the Triumph of Rome - Everitt, Anthony (London John Murray, 2007)
Plucked as teenager from provincial obscurity by his great-uncle Julius Caesar, who adopted him posthumously in his will, Caesar Augustus transformed the chaotic Republic into an orderly imperial autocracy. His consolidation of the Roman empire arguably laid the foundations of Europe. Although a sickly young man, with a tendency to fall seriously ill at moments of crisis, Augustus taught himself to be brave and was intelligent, painstaking and patient. He worked extraordinarily hard, and, within a generation, had rebuilt Rome, transforming it into a splendid metropolis and centre for civil government and the arts. In this biography, Anthony Everitt uncovers the deeply human character of this extraordinary man. It is also an exhilarating portrait of Roman social customs and politics
Include Map and Index
Keywords: Augustus, Emperor of Rome, 63 B.C.-14 A.D -- Rome (Empire) -- Emperors